Analysis of PD-1/PD-L1 Inhibitors Utilization in the Treatment of Advanced/Metastatic Non-small Cell Lung Cancer - Thi Hong Hanh, Nguyen; Thi Thanh Minh, Nguyen; Thi Dieu Huyen, Le; Thi Thu Trang, Tran; Quynh Chi, Nguyen; Thi Thuy Hong, Nguyen; Thanh Hai, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2026)
Abstract: Objective: to analyze the utilization patterns of PD-1/PD-L1 inhibitors in the treatment of non-small cell lung cancer (NSCLC) at the K Hospital and to assess the compliance with clinical practice guidelines. Subjects and methods: a retrospective descriptive study was conducted on medical records of patients aged ≥18 years diagnosed with advanced-stage NSCLC who received PD-1/PD-L1 inhibitors at the K Hospital between January 2024 and July 2025. Treatment appropriateness was assessed based on the National Comprehensive Cancer Network (NCCN) Guidelines v8.2025, the European Society for Medical Oncology (ESMO) Guidelines v1.2.2025, the Vietnamese Ministry of Health (MOH) 2018, and the approved product information at the hospital. Results: A total of 44 patients receiving Atezolizumab and 74 patients receiving Pembrolizumab were analyzed. Atezolizumab was indicated in accordance with ESMO recommendations with the same rate of 89.7% for monotherapy and 100% for combination therapy. Meanwhile, the concordance rates for Pembrolizumab with these guidelines were 64.3% and 71.4% for monotherapy, and 75% and 78.3% for combination therapy, respectively. Dosing appropriateness was 100% for Atezolizumab and 98.7% for Pembrolizumab. However, improper reconstitution concentrations were identified in 45.6% of Pembrolizumab cycles and 4.8% of Atezolizumab cycles. Conclusion: the use of PD-1/PD-L1 inhibitors at the K Hospital showed generally good adherence to international and national guidelines. Nevertheless, it is necessary to strengthen clinical pharmacy activities to ensure the effective and safe use of PD-1/PD-L1 inhibitors. Keywords: Non-small cell lung cancer, PD-1/PD-L1 inhibitors, advanced stage , metastatic stage.